KEMAMPUAN LITERASI DIGITAL GURU SEJARAH DALAM PENGGUNAAN MEDIA PEMBELAJARAN PADA SAAT PANDEMI COVID-19 (STUDI DESKRIPTIF TERHADAP GURU SEJARAH DI SMAN 1 CIWIDEY) - Allisa Pujiyanti, - (2022)
This thesis is entitled "The Digital Literacy Ability of History Teachers in Using Learning Media During the Covid-19 Pandemic (Descriptive Study of History Teachers at SMAN 1 Ciwidey)". This research is motivated by the findings of researchers at the research location that teacher literacy skills are needed, one of which is in terms of using digital learning media. So the study in this research is teacher literacy in using learning media. With the main problem formulation "What is the picture of teacher digital literacy during the COVID-19 pandemic?" This study uses a descriptive study that aims to obtain a description of the literacy that history teachers have in using and developing digital learning media. This includes studying the constraints and efforts as well as student responses to the developed media. The results of this study indicate that teachers have developed digital learning media which are realized in several forms, such as slides, book creators, Smart Apps Creator SAC, padlets. One of them is caused by the obstacles felt by the teacher both from internal and external factors. However, students still feel helped by the media developed by the teacher to understand the material presented, but it does not mean that all students feel that the media is interesting. This is largely determined by what media the teacher develops and uses during the online learning process Keywords: teacher literacy; instructional Media; history learning; online learning.